If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8w + 8)(4w + 4) = 180 Reorder the terms: (8 + 8w)(4w + 4) = 180 Reorder the terms: (8 + 8w)(4 + 4w) = 180 Multiply (8 + 8w) * (4 + 4w) (8(4 + 4w) + 8w * (4 + 4w)) = 180 ((4 * 8 + 4w * 8) + 8w * (4 + 4w)) = 180 ((32 + 32w) + 8w * (4 + 4w)) = 180 (32 + 32w + (4 * 8w + 4w * 8w)) = 180 (32 + 32w + (32w + 32w2)) = 180 Combine like terms: 32w + 32w = 64w (32 + 64w + 32w2) = 180 Solving 32 + 64w + 32w2 = 180 Solving for variable 'w'. Reorder the terms: 32 + -180 + 64w + 32w2 = 180 + -180 Combine like terms: 32 + -180 = -148 -148 + 64w + 32w2 = 180 + -180 Combine like terms: 180 + -180 = 0 -148 + 64w + 32w2 = 0 Factor out the Greatest Common Factor (GCF), '4'. 4(-37 + 16w + 8w2) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-37 + 16w + 8w2)' equal to zero and attempt to solve: Simplifying -37 + 16w + 8w2 = 0 Solving -37 + 16w + 8w2 = 0 Begin completing the square. Divide all terms by 8 the coefficient of the squared term: Divide each side by '8'. -4.625 + 2w + w2 = 0 Move the constant term to the right: Add '4.625' to each side of the equation. -4.625 + 2w + 4.625 + w2 = 0 + 4.625 Reorder the terms: -4.625 + 4.625 + 2w + w2 = 0 + 4.625 Combine like terms: -4.625 + 4.625 = 0.000 0.000 + 2w + w2 = 0 + 4.625 2w + w2 = 0 + 4.625 Combine like terms: 0 + 4.625 = 4.625 2w + w2 = 4.625 The w term is 2w. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2w + 1 + w2 = 4.625 + 1 Reorder the terms: 1 + 2w + w2 = 4.625 + 1 Combine like terms: 4.625 + 1 = 5.625 1 + 2w + w2 = 5.625 Factor a perfect square on the left side: (w + 1)(w + 1) = 5.625 Calculate the square root of the right side: 2.371708245 Break this problem into two subproblems by setting (w + 1) equal to 2.371708245 and -2.371708245.Subproblem 1
w + 1 = 2.371708245 Simplifying w + 1 = 2.371708245 Reorder the terms: 1 + w = 2.371708245 Solving 1 + w = 2.371708245 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + w = 2.371708245 + -1 Combine like terms: 1 + -1 = 0 0 + w = 2.371708245 + -1 w = 2.371708245 + -1 Combine like terms: 2.371708245 + -1 = 1.371708245 w = 1.371708245 Simplifying w = 1.371708245Subproblem 2
w + 1 = -2.371708245 Simplifying w + 1 = -2.371708245 Reorder the terms: 1 + w = -2.371708245 Solving 1 + w = -2.371708245 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + w = -2.371708245 + -1 Combine like terms: 1 + -1 = 0 0 + w = -2.371708245 + -1 w = -2.371708245 + -1 Combine like terms: -2.371708245 + -1 = -3.371708245 w = -3.371708245 Simplifying w = -3.371708245Solution
The solution to the problem is based on the solutions from the subproblems. w = {1.371708245, -3.371708245}Solution
w = {1.371708245, -3.371708245}
| (x-26)+(4x-294)+(.5x+16)=180 | | 5(s+9)+5=2s-6 | | 1=x-24 | | 5x+4x+6=-3 | | 0.5(4z+7+6.1)=0.6(4z-4) | | 180=7x+4+5x+3+2x+5 | | 34=5x+1 | | 4y=6-2x | | 5(x-3)=5x-3 | | 400x-370x=1540 | | 400x+370x=1540 | | 60x=75x-825 | | 180=2x+x+90 | | f(x)=x+2x+15 | | (x-4)(x^2-x-20)=0 | | 60x=75x-11 | | 60x+75x=11 | | (x-4)=(3x+2) | | 6x^2-6x-18=0 | | 4.9x^2+20x+1=5 | | 80x+90x=680 | | 80x+90x=680 | | 0=5t^2+2 | | x+.05=1 | | 2.5x+4.5(462-x)=1441 | | c=jp | | 11-3m=5 | | 11-3m=6 | | 11-3m=12 | | 3x+2y+5y-4y-8x= | | 4(x+4)+6=7x-3(x-5) | | .25x+.5(63-x)=21.25 |